2009
DOI: 10.1038/ismej.2009.82
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of the microbiota of mass-reared Mediterranean fruit flies Ceratitis capitata (Diptera: Tephritidae) improves sterile male sexual performance

Abstract: The sterile insect technique (SIT) is a method of biological control whereby millions of factory reared sterile male insects are released into the field. This technique is commonly used to combat the Mediterranean fruit fly (Ceratitis capitata, Diptera: Tephritidae). Sterile medfly males are less competent in attracting and mating with wild females, a property commonly linked to the irradiation process responsible for the sterilization. As bacteria are important partners in the fly's life cycle, we used molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
219
1
13

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(241 citation statements)
references
References 42 publications
(47 reference statements)
8
219
1
13
Order By: Relevance
“…Ben-Ami et al [15] demonstrated that the C. capitata gut population of Klebsiella species decreased significantly after fly sterilization; the addition of K. oxytoca to the post-irradiation diet markedly improved sterile male performance in copulation tests. Klebsiella spp.…”
Section: Resultsmentioning
confidence: 99%
“…Ben-Ami et al [15] demonstrated that the C. capitata gut population of Klebsiella species decreased significantly after fly sterilization; the addition of K. oxytoca to the post-irradiation diet markedly improved sterile male performance in copulation tests. Klebsiella spp.…”
Section: Resultsmentioning
confidence: 99%
“…Members of this group have been shown to play very important roles in courtship and reproduction. Klebsiella oxytoca has been shown to improve on the mating competitiveness in the medfly38. Klebsiella pneumonia , Citrobacter feundii and Enterobacter cloacae have been shown to act as attractive lures for Tephritidae10394041.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the diversity of bacteria occupying Bactrocera dorsalis vary across different life stages of the fly (Andongma et al 2015). The sterilizing irradiation affected the gut bacterial community structure of the Mediterranean fruit fly C. capitata (Ami et al 2010). House fly larvae may be a sustainable protein source, and the gut microbiota of these larvae represents an intriguing area of study for microbial ecology that will provide opportunities for research on the impact of microbial communities on poultry and fish.…”
Section: Discussionmentioning
confidence: 99%